Coordenação modular: sistematização de orientações no processo projetual arquitetônico - Pauli, Guilherme Penning (2023)
The civil construction industry presents an incessant search for practices that aim to improve its processes, being increasingly valued methods that bring greater efficiency and cost reduction, with a view to a greater rationalization of resources. Modular coordination is perceived as a facilitator and means of interrelationship between components of different origins, where the union of these elements can be foreseen in the design phase, providing opportunities for the relationship of the measures foreseen in the project with the measures present in the industrial production of civil construction components without giving up questions of proportion and geometric composition. In this context, this research presents a mapping following the BPMN standard of the architectural design process for buildings, organized into 6 phases - dealing with product design and post-delivery of the work, highlighting the necessary activities in each of them, as well as the involved in its realization. In addition to allowing a global view of the process, the main contribution of this mapping is the identification of support materials that can help in its development – norms, theses and dissertations, articles, books – bringing definitions that involve the adoption of the principles of modular coordination. Through the systematization of guidelines, this study contributes so that rationalization through modular coordination becomes more widespread among professionals in the area, bringing knowledge to be inserted in the design stage of buildings, thus avoiding rework and recurrent changes during the stage of execution.